Statement of the Uterus Commission of the Gynecological Oncology Working Group (AGO) on the use of primary chemoimmunotherapy to treat patients with locally advanced or recurrent endometrial cancer = Stellungnahme der Kommission Uterus der Arbeitsgemeinschaft Gynäkologische Onkologie (AGO) zur primären Chemo- Immuntherapie bei Patientinnen mit lokal fortgeschrittenem oder rezidiviertem Endometriumkarzinom - Tempfer, Clemens; Brucker, Sara; Juhasz-Böss, Ingolf Hardy Geza; Mallmann, Peter; Steiner, Eric; Denschlag, Dominik; Hillemanns, Peter; Wallwiener, Markus; Beckmann, Matthias Wilhelm (Geburtshilfe und Frauenheilkunde, 2023)
The publication of two large randomized studies - the ENGOT-EN-6-NSGO/GOG-3031/RUBY trial and the NRG-GY018 trial - which investigated combining chemotherapy with immunotherapy to treat patients with primary advanced or recurrent endometrial cancer (EC) has transformed the clinical study landscape in terms of first-line therapy for affected patients and has set a new standard of therapy. In the ENGOT-EN-6-NSGO/GOG-3031/RUBY trial, the addition of dostarlimab to standard chemotherapy with carboplatin and paclitaxel resulted in. In the NRG-GY018 trial, the addition of pembrolizumab to standard chemotherapy with carboplatin and paclitaxel resulted in As expected, the effect in both trials was much more pronounced in the group of patients with dMMR/MSI-high tumors. According to the assessment of the Uterus Organ Commission of the AGO, all patients with dMMR/MSI-high tumors should receive chemoimmunotherapy and all patients with pMMR/MSI-low tumors who meet the inclusion criteria of the two trials discussed here may have chemoimmunotherapy.
Gesehen am 06.08.2024